Modificação do Poli(hidroxibutirato) PHB com nucleantes e com o copolímero (etileno-co-acetato de vinila) - EVA - Falcone, Daniele Maria Bruno (Universidade Federal de São Carlos, 2008)
In this work, we sought to modify PHB, processing it in the melted state, and to evaluate the effect of the modifications on its mechanical properties and biodegradation characteristics. The following systems were therefore studied: a PHB/EVA blend, in a 90/10 ratio, with an ethylene-co-vinyl acetate copolymer containing 28% of VA; a PHB and PHB/EVA blend with 1% of Boron Nitride (BN) nucleant; a PHB and PHB/EVA blend with 0,35% of HPN nucleant ( Hyperform Nucleant ); and a PHB/EVA blend with 5% of Elvaloy PTW, which was used as a compatibilizer. These systems were characterized by thermal, mechanical, morphological and biodegradation analyses using the following techniques: Melt Flow Index (MFI), Differential Scanning Calorimetry (DSC), Thermogravimetry (TG), Dynamic Mechanical Thermal Analysis (DMTA), Size Exclusion Chromatography (SEC), Tensile Mechanical and Izod Impact (notched) Tests, Wide-Angle X-ray Diffraction (WAXD), Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM). The biodegradability test involved burying the samples in a suitable compost for 60, 120 and 180 days. The DCS analysis indicated that Boron Nitride was an effective nucleating agent for the PHB. However, the HPN did not act as a nucleant on this polymer, but instead, induced degradation of the PHB upon heating, as indicated by MFI, DSC and TG. Moreover, the addition of BN or even EVA did not improve the mechanical properties of PHB, and Elvaloy PTW did not act as a compatibilizing agent for the PHB/EVA blend. The HPN was found to interact antagonically with the PHB, which displayed extremely low impact strength values and widely dispersed results. The SEM and AFM analyses revealed poor distribution and inadequate dispersion of EVA in the PHB matrix. In addition, the AFM technique indicated that the PHB topography displayed the presence of pores, which undoubtedly, combined with the other factors, hindered its modification. Biodegradation was found to be strongly composition-dependent, since the addition of 10% of EVA to the PHB significantly accelerated the degradation of the PHB in this blend. In other words, the PHB probably exhibited disordered chain packing in the proximities of the EVA, facilitating the process of biodegradation by microorganisms. Hence, this study demonstrated the difficulty of modifying PHB, since it involves a variety of factors, as well as the possibility of developing PHB-based materials that biodegrade more or less rapidly according to the needs of a specific application.
Keywords: Polímeros; Poli (Hidroxibutirato); Biodegradação; Agentes nucleantes; Blendas poliméricas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA